Physiological evaluation of sleep surfaces in healthy volunteers and patients with acute-upon-chronic lower back pain - Hulse, Bronwyn Leigh (Division of Exercise Science and Sports Medicine, 2023)
Studies have documented that the use of a lumbar support while in the sitting position results in reduced back and leg pain, centralisation of pain and reduced erector spinae muscle activity in patients with lower back pain (LBP). While the positive effects of a lumbar support in sitting have been studied, few researchers have attempted to document the value of such a support in the supine position. Since many patients with LBP suffer from insomnia and nocturnal discomfort, it may be possible that the use of a foam surface overlay could positively influence their symptoms. Several foam surface overlays are currently used as a popular form of management for patients presenting with LBP. These include the convoluted foam surface ("egg box'' shape), which to my knowledge has not been scientifically studied and the lumbar body support, the value of which has only recently been reported. That study found that patients with chronic LBP have decreased electromyographic (EMG) activity of the erector spinae muscles, lower heart rates (HR) and decreased perception of discomfort (ROD) when lying on this locally designed, triple density, contoured, lumbar body support system (LBS) compared with a conventional flat innerspring mattress (CM). Accordingly the aim of this thesis was to measure the EMG activity, heart rate response, perception of comfort and pattern of pressure distribution after lying on a variety of different surfaces, thus endeavouring to determine a mechanism of action of the LBS. In the first study of this thesis, ten patients with LBP were exposed to a random order, 30 minute period on three sleep surfaces: Lumbar body support on top of a conventional mattress (LBS+ CM), 60 mm convoluted foam surface on top of a conventional mattress (CFS + CM), and a conventional mattress (CM) alone. Each patient acted as his/her own control. Recordings of EMG activity, HR and ROD were measured for each patient. Average HR over the 30 minute period was lower after acute exposure to the LBS+ CM (60 ± 11 b/min) compared to the CM (66 ± 10 b/min, p < 0.05; LBS+ CM vs. CM). Although average HR response to the LBS+ CM was lower compared to CFS + CM (64 ± 9 b/min), this difference was not significant. ROD reported after acute exposure to the LBS+ CM was improved (1.9 ± 0.7 units), compared to the CFS+ CM (3.9 ± 1.0 units) and CM (4.7 ± 2.2 units; p < 0.05). Average EMG activity was lower after 30 minutes on the LBS + CM (2.68 ± 1.1 mv) compared to the CFS+ CM (4.46 ± 2.7 mv) and CM (4.19 ± 2.4 mv; p < 0.05). These results suggest that patients with LBP have reduced EMG activity and HR measurements with lower ROD when lying on a LBS + CM compared with a CM and CFS + CM. The second series of experiments involved a further ten patients with lower back pain, who were required to lie supine in random order on the LBS + CM, on a polystyrene mould (PM) (identical to the shape of the LBS) and on a CM. Recordings of EMG activity, HR and ROD were measured for each patient. Average HR over the 30 minute period was lower on the LBS + CM (60 ± 7 b/min) vs. PM + CM (66 ± 10 b/min) and CM (68 ± 9 b/min; p < 0.01 ). Average ROD was improved when patients lay on the LBS+ CM (1.8 ± 0.6 units) vs. PM + CM (5. 7 ± 2.5 units) and CM (4.1 ± 1.8 units; p < 0.05). Furthermore, average EMG activity was significantly reduced after lying on the LBS + CM (2.5 ± 1.0 mv) vs. PM + CM (4.3 ± 1.9 mv) and CM (4.6 ± 1.8 mv; p < 0.01 ). The findings of this study mirror our initial findings. The elevated EMG activity, heart rate and perception of discomfort after lying on a PM suggests that it could be a combination of both the correct density and the correct contour features that is important in reducing muscle spasm in patients with acute-upon-chronic lower back pain. Average HR over the 30 minute period was lower after acute exposure to the LBS+ CM (60 ± 11 b/min) compared to the CM (66 ± 10 b/min, p < 0.05; LBS+ CM vs. CM). Although average HR response to the LBS+ CM was lower compared to CFS + CM (64 ± 9 b/min), this difference was not significant. ROD reported after acute exposure to the LBS+ CM was improved (1.9 ± 0.7 units), compared to the CFS+ CM (3.9 ± 1.0 units) and CM (4.7 ± 2.2 units; p < 0.05). Average EMG activity was lower after 30 minutes on the LBS + CM (2.68 ± 1.1 mv) compared to the CFS+ CM (4.46 ± 2.7 mv) and CM (4.19 ± 2.4 mv; p < 0.05). These results suggest that patients with LBP have reduced EMG activity and HR measurements with lower ROD when lying on a LBS + CM compared with a CM and CFS + CM. The second series of experiments involved a further ten patients with lower back pain, who were required to lie supine in random order on the LBS + CM, on a polystyrene mould (PM) (identical to the shape of the LBS) and on a CM. Recordings of EMG activity, HR and ROD were measured for each patient. Average HR over the 30 minute period was lower on the LBS + CM (60 ± 7 b/min) vs. PM + CM (66 ± 10 b/min) and CM (68 ± 9 b/min; p < 0.01 ). Average ROD was improved when patients lay on the LBS+ CM (1.8 ± 0.6 units) vs. PM + CM (5. 7 ± 2.5 units) and CM (4.1 ± 1.8 units; p < 0.05). Furthermore, average EMG activity was significantly reduced after lying on the LBS + CM (2.5 ± 1.0 mv) vs. PM + CM (4.3 ± 1.9 mv) and CM (4.6 ± 1.8 mv; p < 0.01 ). The findings of this study mirror our initial findings. The elevated EMG activity, heart rate and perception of discomfort after lying on a PM suggests that it could be a combination of both the correct density and the correct contour features that is important in reducing muscle spasm in patients with acute-upon-chronic lower back pain. body support is altered and pressures are more equally distributed when compared to the pressure distribution of the other surfaces measured, without increases in pressure at any point on the body. Similar average and peak pressure results were obtained for the 90 mm CFS + CM and LBS. Since these results were not mirrored by the 60 mm CFS, the thickness of a foam surface possibly plays a role in reducing pressure. The data of these three separate studies could have implications in the adjunctive treatment of i)low back pain and ii) pressure sores. Firstly, the results of this thesis suggest that the use of a 60 mm foam overlay may not be the optimum form of management for patients presenting with paraspinal muscular spasm. Further, it is postulated, that the density and contour features of the lumbar body support are likely to play a role in reducing EMG activity and heart rate, while improving perception of comfort compared to the flat surfaces (CM and 60 mm CFS), which offer little support to the lumbar region of these patients. X Secondly, either the LBS or 90 mm CFS are likely to reduce the incidence of pressure sores in patients required to lie supine for prolonged periods, due to the reduction in peak and average pressures. In view of the contoured surface, it is unlikely that pressure sores could develop in patients lying on the LBS. This hypothesis needs to be confirmed in longer term studies in patients who are severely debilitated or paraplegic, as they are often most at risk for the development of pressure sores.